Techno-Societal 2016 Proceedings of the International Conference on Advanced Technologies for Societal Applications (Springer International Publishing, 2018)
This volume originates from the proceedings of a multidisciplinary conference, Techno-Societal 2016 in Maharashtra, India, that brings together faculty members of various engineering colleges to solve Indian regional relevant problems under the guidance of eminent researchers from various reputed organizations. The focus is on technologies that help develop and improve society, in particular on issues such as the betterment of differently abled people, environment impact, livelihood, rural employment, agriculture, healthcare, energy, transport, sanitation, water, education. This conference aims to help innovators to share their best practices or products developed to solve specific local problems which in turn may help the other researchers to take inspiration to solve problems in their region. On the other hand, technologies proposed by expert researchers may find applications in different regions. This back and forth process for local-global interaction will help in solving local problems by global approach and help in solving global problems by improving local conditions.